Plastic obsession among Malaysian tourists: how far is it true? - Md Zaliki, Najiyah; Saad, Mazni (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh Campus, 2019)
Plastic pollution is one of the prevalent global crises of the decade. The non-degradable nature of plastics has caused severe marine and land pollution which is responsible for the death of hundreds of marine species and birds. Over the years, the generation of plastic waste shows no sign of slowing down and The United Nations have predicted that the amount of plastic in the ocean would weigh more than fishes by 2050. The tourism industry greatly depends on the natural environment as one of its main resources to thrive. In contrast, tourism is also known to generate a great amount of waste to the environment making it as one of the contributors to this crisis. The depletion of environment would give adverse impact on the growth of tourism to a destination. It is a vicious cycle that should be stopped in ensuring the sustainability of a destination and tourism as a whole. This study is in line with targets developed under the Sustainable Development Goals (SDG) 12 established by the United Nations that aims to substantially reduce waste production by 2030. This study intends to understand an untapped angle of the issue, from the perspective of Malaysian tourists as tourism consumers. In this study, the practice of tourists prior to travelling will be assessed to understand its influence on tourists’ behaviour in regard to plastic usage during travels. By understanding tourists’ behaviour, the authorities in a tourism destination could take measures that will encourage sustainable tourism practices among tourists while enjoying tourism growth and sustaining the destination in the long run.